Investigation of stator/rotor pole number combinations in field-modulated permanent magnet machine - Fangfang Bian; Shuaiwei Huang; Caifei Ke (Journal of Physics Communications)
This paper investigates the fluence of stator/rotor pole number combinations on electromagnetic performance of field-modulated permanent-magnet (FMPM) machines. These machines employ the spoke-type PM and the consequent-pole PM as the rotor. Firstly, the configuration and operating principle of the FMPM machine are briefly illustrated, followed by systematic demonstration of pole-selection and winding configuration methodologies based on field modulation theory. Under constant machine dimensions and PM volume constraints, the torque characteristics—including average torque, cogging torque, and torque ripple—across different slot-pole combinations are comprehensively evaluated by the finite element analysis (FEA). The results demonstrates that the 12-slot/10-pole (12s10p) configuration achieves better electromagnetic performance: the output torque increases while torque ripple and cogging torque reduce to 9.07% and 1.57 Nm respectively, with PM utilization efficiency significantly improved.